Partner market and union stability in Germany - Stauder, Johannes; Unsöld, Laura (Theorie als Beruf, 2021)
This study investigates whether the imbalance of supply and competitors on the partner market impacts the stability of marital and non-marital unions. Using the first six waves of the German Family Panel (pairfam) we find partner market effects on the proposal of a separation and on separation itself. Women’s partner market opportunities impact union stability depending on the duration of the union. The impact of men’s partner market opportunities on union stability depends on living arrangement with the effect being stronger for cohabiting than for married couples. Whether or not a context provides opportunities for (alternative) partner choice and for separation depends on using adequate bridging assumptions about individuals’ preferences for a (new) partner’s traits.
Gesehen am 11.05.2021